2011
DOI: 10.1111/j.1475-679x.2011.00431.x
|View full text |Cite
|
Sign up to set email alerts
|

Private Control Benefits and Earnings Management: Evidence from Insider Controlled Firms

Abstract: We examine earnings management practices of insider controlled firms across 22 countries to shed light on the link between consumption of private benefits and earnings management. Insider controlled firms are associated with more earnings management than noninsider controlled firms in weak investor protection countries. Consistent with the private benefits motive, insider controlled firms with greater divergence between cash‐flow rights and control rights are associated with more earnings management in these c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
112
3
1

Year Published

2012
2012
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 205 publications
(131 citation statements)
references
References 68 publications
(188 reference statements)
7
112
3
1
Order By: Relevance
“…The coefficient on DIV is positive and significant in the AEM (REM) regression when the legal regime stringency is measured by LAW1 ( LAW2 ), and insignificant in other columns. The results in column (4) (i.e., in the REM regression with LAW2 ) are consistent with our earlier evidence in Table and results in prior research (Haw et al ; Gopalan and Jayaraman ).…”
Section: Sample Data and Empirical Resultssupporting
confidence: 91%
See 1 more Smart Citation
“…The coefficient on DIV is positive and significant in the AEM (REM) regression when the legal regime stringency is measured by LAW1 ( LAW2 ), and insignificant in other columns. The results in column (4) (i.e., in the REM regression with LAW2 ) are consistent with our earlier evidence in Table and results in prior research (Haw et al ; Gopalan and Jayaraman ).…”
Section: Sample Data and Empirical Resultssupporting
confidence: 91%
“…Two competing predictions exist regarding the effect of legal regimes on REM. Previous research shows that the magnitude of accrual‐based earnings management (AEM) decreases as the country‐level legal regime strengthens because effective investor protection weakens managerial incentives to manipulate earnings via AEM (e.g., Gopalan and Jayaraman ; Haw et al ). In a similar vein, one can predict that the magnitude of REM decreases as the legal regime becomes stronger.…”
Section: Introductionmentioning
confidence: 99%
“…When asked to quantify RPTs as a percentage of sales, 67% (20%) of firms with RPTs reported that RPTs were at least 1% (5%) of revenue. In a later study covering data of 4517 unique firms from 22 countries across Europe and Asia, Gopalan and Jayraman (2012) confirm tunnelling activities in insider controlled 43 corporations and report that such companies operating in low investor protection countries are associated with more earnings management than their non-insider controlled counterparts and that the extent of earnings management within insider controlled firms was increasing in the extent of divergence between cash flow rights and control rights. In a related vein, George and Kabir (2008) report evidence of profit redistribution among firms affiliated to Indian Business Groups.…”
Section: Related Party Transactionsmentioning
confidence: 85%
“…Such diversion takes the form of "looting" (La Porta et al, 2003). Even when business groups do not have an in-house bank as is the case in countries such as India, Gopalan, Nanda, and Seru (2008) document the use of internal capital markets wherein intra-group loans among the firms affiliated to a group serve as a channel for transfer of financial resources between business group firms. agency costs.…”
Section: Executive Compensationmentioning
confidence: 98%
“…Clustering coefficient is called clustering coefficient, it measure extent network group and crucial parameter [12,13]. In terms of social networks, the group is a very important form of clustering coefficient characteristics, the group is also known as the cluster phenomenon, for which scientists are clustering coefficient of concepts presented [14].…”
Section: Characteristics Of Complex Network Metricsmentioning
confidence: 99%